Efficient determination of consensus secondary structures in RNA - Nguyen, Truong (University of Ottawa (Canada), 2004)
Transcription and translation are critical steps through which genetic expression occurs. Whereas there exists research for computationally determining the primary structure binding sites for transcription, research into the computational elucidation of secondary structure binding sites for translation has not been as thoroughly conducted. The approach proposed involves first selecting a single sequence from a set of data sequences. From this sequence, all biological palindromes are determined. Using these palindromes, all possible candidate secondary structure motifs with minimum support are assembled, formulating the solution space. The motifs in the solution space are reduced to structural form. These structures are searched against the remaining sequences. Negative matches are discarded, while positive matches converge to consensus secondary structure motifs by specification of constituent base pairs. Positively matched motifs are ranked according to the amount of information content. The analysis techniques presented yielded promising results. Consensus secondary structures were successfully elucidated from the source sequences given appropriate constraints.
Keywords: Biology, Molecular.; Engineering, Electronics and Electrical.